Analisis Penguatan Sistem Pemasyarakatan Melalui Konsep Reintegrasi Sosial - Hermi Asmawati (Jurnal Mengkaji Indonesia, 2022)
Abstract: Law Number 12 of 1995 concerning Corrections was originally implemented as an instrument to complement the correctional system. However, even though the spirit of the law aims to replace the prison system that has lasted for a long time, over time the law has begun to experience deficiencies and weaknesses. Law Number 12 of 1995 has raised many pros and cons regarding its implementation, thus making the government try to make changes on the basis of the premise that this law can no longer adapt to the times and is difficult to answer problems in the field of penitentiary which are increasingly complex in the contemporary era. Purpose: Analyze the concept of social reintegration between the old and new Correctional Law. Design/Methodology/Approach: This research uses normative legal methods and literature study methods. The approach used is the approach of statutory regulations (statute approcah). Findings: Law Number 22 of 2022 concerning Corrections perfects the previous Corrections Law. Law Number 22 of 2022 further strengthens the shift in the concept of treatment of prisoners to focus more on the concept of social reintegration today which focuses on creating justice, balance, restoration of relations, legal protection, and guarantees for the human rights of prisoners, children, convicts, foster children, victims, and society. The new Correctional Law seeks to restore the dignity of convicts and child prisoners in society and to be accepted by society and victims. Originality/Value: No one has yet discussed Law Number 22 of 2022